Risiko Infeksi COVID-19 Pada Tenaga Kesehatan - Ciuputri, Pauline; Isfandiari, Muhammad Atoillah; Nugroho, Anita Puspitasari Dyah; Hendrawati, Nunung; Herlina, Herlina; Murtiani, Farida (Jurnal Kesehatan Komunitas, 2024)
Healthcare workers are one of the groups at risk of COVID-19 infection. This study aims to determine the incidence of COVID-19 infection among healthcare workers in the Hospital. The research method used is cross-sectional. The study was conducted at Sulianti Saroso Infectious Disease Hospital (SSIDH) in March 2022. The sample in this study consists of healthcare workers at SSIDH who were infected with COVID-19, totaling 234 people. The source of secondary data is surveillance reports of healthcare workers infected with COVID-19 based on data from January-February 2022. The independent variable is the unit of work, and the dependent variable is COVID-19 infection. Data analysis was done univariately and bivariately. The results show that the majority of COVID-19 infections occurred in the category of more than 1x (>1x) with a total of 119 subjects (50.8%). High-risk work units in this study are the ICU, ER, Radiology, Laboratory, Central Surgical Installation, and negative pressure care rooms. Further analysis using the Chi-Square test yielded a P-value of 0.000. The conclusion drawn is that there is a relationship between work units and COVID-19 infection among healthcare workers.